Letter from Townsville - Silver, Anneke; McBurnie, Ron (LiNQ (Literature in North Queensland), 2016)
This letter will focus on five practising artists who are also full-time teachers at the Townsville T.A.F.E. Because of their position at the inception of students’ artistic careers they contribute in a basic and vital way to the expanding art community in the North.